DIFFERENCE BETWEEN ZIRCONIUM CROWNS AND STAINLESS STEEL CROWNS IN PREMOLAR PROSTHETICS - Бурхонова Зарафруз Кобиловна; Хайдаров Улугбек (American Journals, 2023)
One of the reasons for the rejection of the use of CAD/CAM technologies in dentistry is reports of the insolvency of all-ceramic frame restorations made of polycrystalline ceramics based on zirconium dioxide and chipped veneers [1, 2]. The discrepancy in the recommendations for the manufacture of frame all-ceramic restorations raises a number of questions. Sandblasting is still widely used to improve surface roughness, strengthen bonding between the veneer and the frame and increase the strength of the connection during cementing.